A greener faith religious environmentalism and our planet's future - Gottlieb, Roger S. (Oxford ; New York : Oxford University Press, 2006)
In a time of darkening environmental prospects, frightening religious fundamentalism, and moribund liberalism, the remarkable and historically unprecedented rise of religious environmentalism is a profound source of hope. Theologians are recovering nature-honoring elements of traditional religions and forging bold new theologies connecting devotion to God and spiritual truth with love for God's creation and care for the Earth. And religious people throughout the world are transforming the meaning of their faiths in the face of the environmental crisis. The successes and significance of religious environmentalism are manifest in statements by leaders of virtually all the world's religions, in new and "green" prayers and rituals, and in sophisticated criticisms of modern society's economy, politics, and culture. From the Evangelical Environmental Network to the Buddhist prime minister of Mongolia, the National Council of Churches to tree-planting campaigns in Zimbabwe, religious environmentalism has become a powerful component of the world environmental movement. In A Greener Faith, Roger S. Gottlieb chronicles the promises of this critically important movement, illuminating its principal ideas, leading personalities, and ways of connecting care for the earth with justice for human beings. He also shows how religious environmentalism breaks the customary boundaries of "religious issues" in political life. Asserting that environmental degradation is sacrilegious, sinful, and an offense against God catapults religions directly into questions of social policy, economic and moral priorities, and the overall direction of secular society. Gottlieb contends that a spiritual perspective applied to the Earth provides the environmental movement with a uniquely appropriate way to voice its dream of a sustainable and just world. Equally important, it helps develop a world-making political agenda that far exceeds interest group politics applied to forests and toxic incinerators. Rather, religious environmentalism offers an all-inclusive vision of what human beings are and how we should treat each other and the rest of life. Gottlieb analyzes the growing synthesis of the movement's religious, social, and political aspects, as well as the challenges it faces in consumerism, fundamentalism, and globalization.
Religion and the human meaning of environmental crisis -- Religion, nature, environment -- Religious environmentalism and secular society -- Sustainable religion -- Religious environmentalism in action -- Environmentalism as spirituality -- Opening the heart : the ritual life of religious environmentalism -- Five faces of religious environmentalism -- Obstacles, prospects, hope.
Includes bibliographical references (p. 245-279) and index.
Description based on print version record.
Keywords: Human ecology -- Religious aspects -- Christianity; Environmentalism -- Religious aspects -- Christianity; Electronic books